TEACHERS’ PERCEPTIONS OF THE CHALLENGES IN THE ONLINE EFL TEACHING: A REVIEW OF PREVIOUS STUDIES - Muthi’ah, Muthi’ah; Nawir, Muhammad Syahruddin; Tsuraya, Annisa Shofa (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract: Technological advances and the COVID-19 have accelerated the shift from traditional learning to online learning. Educational institutions have no choice but to convert the classroom setting into online classes. When teaching online, EFL teachers may have encountered challenges. This paper aims to review some previous studies on the teachers’ perceptions of the challenges in online EFL teaching, in Indonesia and other countries. This study employs library research. The result shows that challenges occurred during the implementation of online EFL teaching and learning. In other countries such as Korea, Thailand, Iran, China, and Saudi Arabia, the challenges are mostly related to the students’ learning process including the time and class management. On the other hand, in Indonesia, the challenges are more complex. Lack of experience with the online teaching methods and the limitations regarding the adequate internet facilities become the challenges that are most complained by the teachers. Abstrak: Kemajuan teknologi dan COVID-19 telah mempercepat peralihan dari pembelajaran tradisional ke pembelajaran online. Institusi pendidikan tidak punya pilihan selain mengubah pengaturan kelas menjadi kelas online. Saat mengajar online, guru EFL mungkin menghadapi tantangan. Makalah ini bertujuan untuk meninjau beberapa penelitian sebelumnya tentang persepsi guru tentang tantangan dalam pengajaran EFL online, di Indonesia dan negara lain. Penelitian ini menggunakan penelitian kepustakaan. Hasil penelitian menunjukkan bahwa tantangan terjadi selama pelaksanaan pembelajaran EFL online. Di negara-negara lain seperti Korea, Thailand, Iran, Cina, dan Arab Saudi, tantangannya lebih banyak terkait dengan proses belajar siswa termasuk waktu dan manajemen kelas. Di sisi lain, di Indonesia, tantangannya lebih kompleks. Kurangnya pengalaman dengan metode pengajaran online dan keterbatasan fasilitas internet yang memadai menjadi tantangan yang paling dikeluhkan oleh para guru.